Effectiveness and safety of Qingfei Dayuan granules for treating influenza and upper respiratory tract infections manifested by the pulmonary heat-toxin syndrome: A multicenter, randomized, double-blind, placebo-controlled trial - Li, Weinan; Xie, Lihan; Zhu, Xiaoyun; Yang, Yi; Wang, Linqun; Yang, Min; Li, Hengfei; Li, Xucheng; Yan, Guangjun; Wu, Xiongfei; Zhao, Weijun; Zhang, Jilong; et al. (Frontiers in Pharmacology, 2023)
Background: Patients diagnosed with influenza and upper respiratory tract infections (URTIs) have similar clinical manifestations and biochemical indices and a low detection rate of viral pathogens, mixed infection with diverse respiratory viruses, and targeted antiviral treatment difficulty in the early stage. According to the treatment strategy of “homotherapy for heteropathy” in traditional Chinese medicine (TCM), different diseases with the same clinical symptoms can be treated with the same medicines. Qingfei Dayuan granules (QFDY), a type of Chinese herbal preparation included in the TCM Diagnosis and Treatment Protocol for COVID-19 of Hubei Province issued by the Health Commission of Hubei Province in 2021, are recommended for patients suffering from COVID-19 with symptoms of fever, cough, and fatigue, among others. Additionally, recent studies have shown that QFDY effectively alleviates fever, cough, and other clinical symptoms in patients with influenza and URTIs. Materials and methods: The study was designed as a multicenter, randomized, double-blind, placebo-controlled clinical trial for treatment for influenza and URTIs manifested by pulmonary heat-toxin syndrome (PHTS) with QFDY. A total of 220 eligible patients were enrolled from eight first-class hospitals in five cities of Hubei Province in China and randomly assigned to receive either 15 g of QFDY or a placebo three times a day for 5 days. The primary outcome was the complete fever relief time. Secondary outcomes included efficacy evaluation of TCM syndromes, scores of TCM syndromes, cure rate of each single symptom, incidence of comorbidities and progression to severe conditions, combined medications, and laboratory tests. Safety evaluations mainly involved adverse events (AEs) and changes in vital signs during the study. Results: Compared with the placebo group, the complete fever relief time was shorter in the QFDY group, 24 h (12.0, 48.0) in the full analysis set (FAS) and 24 h (12.0, 49.5) in the per-protocol set (PPS) (p ≤ 0.001). After a 3-day treatment, the clinical recovery rate (22.3% in the FAS and 21.6% in the PPS) and cure rate of cough (38.6% in the FAS and 37.9% in the PPS), a stuffy and running nose, and sneezing (60.0% in the FAS and 59.5% in the PPS) in the QFDY group were higher than those in the placebo group (p < 0.05). The number of patients taking antibiotics for more than 24 h in the placebo group (nine cases) was significantly higher than that in the QFDY group (one case) (p < 0.05). There were no significant differences between the two groups in terms of scores of TCM syndromes, incidence of comorbidities or progression to severe conditions, combined use of acetaminophen tablets or phlegm-resolving medicines, and laboratory tests (p > 0.05). Meanwhile, no significant difference was found in the incidence of AEs and vital signs between the two groups (p > 0.05). Conclusion: The trial showed that QFDY was an effective and safe treatment modality for influenza and URTIs manifested by PHTS because it shortened the complete fever relief time, accelerated clinical recovery, and alleviated symptoms such as cough, a stuffy and running nose, and sneezing during the course of treatment. Clinical trial registration:https://www.chictr.org.cn/showproj.aspx?proj=131702, identifier ChiCTR2100049695.